Alterações bioquímicas e cardio-respiratórias de Tilápia do Nilo (Oreochromis niloticus) frente à exposição sub-letal ao sulfato de cobre - Neder, Lyandra Mara Zanatta (Universidade Federal de São Carlos, 2005)
The present study evaluated the biochemical, hematological and cardio-respiratory responses of Nile tilapia (Oreochromis niloticus) to copper sulfate (CuSO4). A group of fish (T2; n = 8) was exposed to 50% of a CL50 (48 h) of CuSO4, while the control group (T1; n = 8) was submitted to the same conditions of water quality without CuSO4. Samples of blood, gills, liver, white and red muscles were collected at the end of the experimental period for the following determination: Hematocrit (Hct), hemoglobin (Hb), red blood cells (RBC), mean corpuscular volume (VCM), mean corpuscular hemoglobin (HCM), mean corpuscular hemoglobin concentration (CHCM), Na+/K+-ATPase, metalothionein (MT), glucose, lactate, pyruvate, glycogen, ionic concentrations (Na+, K+ e Cl-) and plasmatic ammonia. The cardio-respiratory parameters (oxygen uptake - &VO2 , O2 extraction from the ventilatory current - EO2, respiratory frequency - fR, gill ventilation - &VG , ventilatory tidal volume - VT, and heart rate - fH). were also measured in both experimental groups during 48 h: When compared to the control group, fish treated with CuSO4 showed a significant increase in Hct, Hb, RBC and VCM. Lactate concentration increased in liver and red muscle. Glucose increased also in liver, but decreased in the muscles, and a reduction on glycogen was observed in all the tissues analyzed. Fish exposed to CuSO4 presented a reduction in EO2 after 3 h and in &VO2 after 6 h. An increase in &VG was detected after 1 h of exposure to CuSO4. This hiperventilation was mainly due to increases in the fR, since the VT remained constant during all the experimental time. Fish treated with CuSO4 also displayed a significant bradycardia after 12 hours of exposure.
Keywords: Fisiologia comparada; Sulfato de cobre; Oreochromis niloticus; Respirometria; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA COMPARADA